Effect of Bee Pollen Addition on the Polyphenol Content, Antioxidant Activity, and Quality Parameters of Honey - Celina Habryka; Robert Socha; Lesław Juszczak (MDPI AG, 2021)
Bee pollen is regarded as a valuable source of bioactive substances. Honey enrichment with bee pollen seems to be the most popular way to introduce this bee product into a human diet. The aim of this study was to determine the influence of the addition of bee pollen to honey on the content of selected biologically active pollen components, antioxidant activity, and quality parameters, as well as sensory properties. On the basis of the obtained results, it was established that enriching honey with bee pollen resulted in a significant increase in the level of phenolics, including both flavonoids and phenolic acids, of which kaempferol and gallic acid were present in the highest level. As a result of increasing addition of bee pollen, an increase in the antioxidative, antiradical, and reducing activities of honey was observed. However, the addition of bee pollen to honey resulted in the deterioration of its sensory properties. A decrease in brightness, clarity, and uniformity of color, as well as a decrease in the perception of fragrance, was observed. In the assessment of texture, a decrease in smoothness and spread ability in the mouth was observed, with a significant increase in the feeling of sandiness. In contrast, the evaluation of taste revealed a marked increase in sharpness, acid taste, bitterness, and persistence of the aftertaste, with a simultaneous decrease in sweetness. Honey enrichment with bee pollen resulted in a significant increase in the content of water-insoluble substances, free acidity, specific conductivity, and proline content, with a slight decrease in the content of glucose and fructose.